2017
DOI: 10.1002/j.0022-0337.2017.81.3.tb06279.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Two Hybrid Instrumentation Techniques in a Dental Student Endodontic Clinic: A Retrospective Study

Abstract: The aim of this study was to retrospectively assess the safety potential of a hybrid technique combining nickel-titanium (NiTi) reciprocating and rotary instruments by third-and fourth-year dental students in the predoctoral endodontics clinic at one U.S. dental school. For the study, 3,194 root canal treatments performed by 317 dental students from 2012 through 2015 were evaluated for incidence of ledge creation and instrument separation. The hybrid reciprocating and rotary technique (RRT) consisted of a glid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…There is a small risk of separation of hand instruments that should be taken into account. 38 Recently, the use of reciprocating instruments was proven to properly clean these canals with minimal risk of incidents. 39 …”
Section: Locating the Mesiobuccal Canal In Primary Treatmentsmentioning
confidence: 99%
“…There is a small risk of separation of hand instruments that should be taken into account. 38 Recently, the use of reciprocating instruments was proven to properly clean these canals with minimal risk of incidents. 39 …”
Section: Locating the Mesiobuccal Canal In Primary Treatmentsmentioning
confidence: 99%
“…Shen et al , [ 30 , 31 ], have presented 0.3% for ProFile instrument files used up to 3 times, and 0.05% for ProFile Vortex files used by graduate students in a single use regimen. Coelho et al , [ 32 ], have presented no instrument separation in an undergraduate endodontic clinic. The NiTi rotary Vortex instruments were used in 3 root canal treatments if no sign of distortion was present [ 32 ].…”
Section: Rotary Kinematicsmentioning
confidence: 99%
“…Coelho et al , [ 32 ], have presented no instrument separation in an undergraduate endodontic clinic. The NiTi rotary Vortex instruments were used in 3 root canal treatments if no sign of distortion was present [ 32 ]. A recent clinical study has shown a separation rate of 0.83% for the Twisted File Adaptive after the use in 3 molars; no instrument separation occurred in the 2 first uses [ 33 ].…”
Section: Rotary Kinematicsmentioning
confidence: 99%
See 2 more Smart Citations